Integrating Numerical Simulation and Experimental Validation to Analyze Temperature Distribution in Friction Stir Welding of Dissimilar Aluminum Alloy - Karanam, Samadhanam Raju; N. Ramanaiah (International Journal of Integrated Engineering, 2024)
In this paper, a 3D finite element model is developed by COMSOL Multiphysics software to study the temperature distribution during the friction stir welding process of dissimilar aluminum alloys AA6351-T6 and AA2024-T351. Dissimilarity comes from the alloying elements with different melting point and latent heat requirements. The input process parameters included different tool rotational speeds (800, 1000 and 1200 rev/min), different welding speeds (0.35, 0.7 and 1.2 mm/s) while keeping the axial load of 3kN constant. High speed steel (HSS) is considered as the tool material and AA6351-T6 and AA2024-T351 are considered to be the workpiece materials. The increase of maximum temperature observed with the increase of the tool rotational speed. Numerical simulations are found to be useful to gain process understanding and conduct process planning as well as tool design.